Interest Rate Ceilings and Agriculture Financing in Kenya - Murungi, Kellen (Graduate School of Business (GSB), 2021)
The agriculture sector in Kenya contributes about 34% of the GDP and is a major employer both formally and informally. The sector has historically experienced challenges in accessing commercial financing, with banks committing less than 5% of their portfolio to agriculture, which has limited the sector's growth. In August 2016, the Kenyan government introduced interest rate ceilings in a bid to reduce the cost of borrowing, thereby releasing more capital to all enterprises, including those in the agricultural sector. This study sought to examine the effect of these interest rate ceilings on the growth in lending to the agricultural sector in Kenya. The study estimated a panel multiple regression model for 26 commercial banks, spanning a 5-year period between 2014 and 2018. The analysis revealed that the amount of credit supply to the agricultural sector increased following the imposition of interest rate ceilings. The findings from the panel regression analysis confirmed that variations in the amount of loans to the agricultural sector were affected by the imposition of interest ceilings. The finding held after controlling for bank-specific characteristics, such as firm size, equity, asset quality, liquidity and interest spread, suggesting that interest rate ceilings, if prudently applied, could lead to increased access to credit for the agricultural sector. However, the subsequent reversal of the interest rate capping law demonstrated that this is a blunt tool for enabling access to credit not only because of its ineffectiveness but due to the fact that it is prone to politicisation. This study, therefore, recommends that the government creates a favourable policy environment that enhances competition and information sharing in the banking sector which will lead to lower costs of credit. If they are deemed necessary, interest rate caps should be selectively used to enhance lending only to sectors where there is sufficient empirical evidence of their effectiveness.